Agamben Reading Kafka: The Animal Way to Paradise - de Boer, Ype; Snoek, Anke (Labyrinth, 2025)
The aim of this paper is to revisit the theme of paradise and animality in the work of Kafka, whilst at the same time elucidate Agamben's complex understanding of these notions with the help of the literary imagery of Kafka. In a world where many find themselves crushed by the anthropological machine, Agamben outlines an intuition Kafka had about animals, that can help humans to reconcile with their animal nature, and let them guide us back to paradise. If animals have never left paradise, and the human realm is not substantially different for the animal realm, then like the animals we have never truly left paradise but only think we did. It is only in trying to uphold a higher, human sphere, through self-subjection and exclusion, that we leave the paradisical realm. Kafka's creatures show us the ridiculousness of these divisions between human and animals.